1985
DOI: 10.1103/physrevlett.55.2712
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Theory on the Entanglement Effect of Rodlike Polymers

Abstract: The rotational diffusion constant Dr of entangled rodlike polymers in semidilute solution was calculated by our refining quantitatively the Doi-Edwards tube model. The methods of probability and stochastic process theory were used to calculate the mean lifetime of tubes, while the mean step angle of jump diffusion was evaluated by computer simulation on the size distribution of tubes. Our result eliminates a large discrepancy of Dr between the Doi-Edwards theory and a variety of experiments on rodlike polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 12 publications
3
47
0
Order By: Relevance
“…Furthermore, a previous study by Bhave has already shown that the k =0 eigenfunction must be nonzero if ␣␤ Ͼ 0. 3 Much of the experimental work 9,10 and theoretical work [11][12][13] on this topic are aimed at describing an effective diffusivity that already includes rod-rod interaction, so these diffusivity values cannot be readily applied to an equation where rodrod interaction is considered separately through ⌽. 3 and allows infinitesimal fluctuations around the isotropic base state for all values of k ജ 0.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a previous study by Bhave has already shown that the k =0 eigenfunction must be nonzero if ␣␤ Ͼ 0. 3 Much of the experimental work 9,10 and theoretical work [11][12][13] on this topic are aimed at describing an effective diffusivity that already includes rod-rod interaction, so these diffusivity values cannot be readily applied to an equation where rodrod interaction is considered separately through ⌽. 3 and allows infinitesimal fluctuations around the isotropic base state for all values of k ജ 0.…”
Section: Resultsmentioning
confidence: 99%
“…For strong suppression, the asymptotic behavior of the self-consistent equation [Eq. (17)] is obtained as D ⊥ /D 0 ⊥ ∼ 36π(n * ) −2 , which defines the normalization n * c,⊥ = 6 √ π for comparison with our simulation results.…”
Section: B Translational Diffusionmentioning
confidence: 88%
“…As a consequence of this high entanglement, the rotational motion and the translational diffusion perpendicular to the needle slow down drastically, whereas the diffusion along the tube is unaffected. In both theory [15][16][17][18][19][20] and computer simulations [21][22][23][24][25][26] the density-dependent scaling behavior of the long-time rotational and perpendicular translational diffusion coefficients have been established and scale with the number density as n −2 . Computer simulations for two-dimensional toy models have also been performed earlier [27][28][29][30][31] and for a needle in the presence of pointlike obstacles one observes the same scaling laws of the transport coefficients as in three dimensions [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Concentration of rods in this case is constant. The effective viscosity η of the solution can be obtained based on the general equation for the stress tensor [23]: Let us consider the regime of a thin liquid jet of radius smaller than the rod length:…”
Section: Most Of the Above Results Cover Solutions Of Flexible Chainsmentioning
confidence: 99%